Anesthetic implications in porphyrias - Randjelovic, Milica; Stojanovic, Milena; Radeka, Jovan; Vasilijic, Milena; Jankovic, Radmilo (Frontiers in Anesthesiology, 2023)
The porphyrias are a group of disorders related to deficient heme biosynthesis, caused by malfunction of certain enzymes in the synthesis pathway. Erythropoietic porphyrias present with cutaneous symptoms and do not affect the nervous system. Hepatic porphyrias develop acute attacks with mild to severe neurovisceral symptoms, dramatic course, and rare, but possibly lethal outcomes. Anesthetic management of patients suffering from hepatic porphyria is challenging regarding the possibility of triggering or worsening the acute attack with medications that induce or maintain anesthesia. The medications are labeled as safe or unsafe according to laboratory experiments, clinical studies, case reports and experience. In this paper, we discuss underlying pathophysiology, presentation, therapy recommendations and anesthetic implications related to porphyrias.